Systematic Literature Review: The Effectiveness Of Using The Problem-Based Learning Model In Improving Problem-Solving Skills - Nuramaliyah Ramadhany; Alimuddin Tampa; Hamzah Upu (Universitas Wiralodra, 2025)
Amid challenges in mathematics education, students' low problem-solving skills have become a key concern. Studies have shown that many students struggle to understand problems, devise appropriate strategies, and validate their solutions, especially when faced with real-world mathematical tasks. Problem-Based Learning (PBL) has been identified in many studies as a promising approach to address this issue. This study aims to evaluate the effectiveness of PBL in enhancing students' mathematical problem-solving skills through a systematic review of recent literature. Using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) method, this Systematic Literature Review (SLR) identified 20 relevant articles from 1,672 collected through databases like ERIC, ScienceDirect, IOP Science, and PubMed, using keywords